PENGELOLAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA ANAK SEKOLAH DASAR DI SDN 1 SUKAPURA LAMPUNG BARAT - Sindi Fahmi Sa’adah; Ahmad Arpan; M Amin Nurfauzi; Ami Latifah (UNISAN JURNAL, 2023)
This exploration expects to make sense of how Islamic Strict Schooling learning is completed at SDN 1 Sukapura, Sumber Jaya Locale, West Lampung Rule. This examination utilizes an illustrative subjective methodology. Perceptions, meetings and documentation were utilized to gather information. The school head, educational plan delegates, PAI instructors, and understudies were the exploration subjects. By and large, the examination results show that the administration of Islamic Strict Instruction learning at SDN 1 Sukapura, Sumberjaya Area, West Lampung Regime has met the educational plan necessities. PAI instructors are answerable for arranging and executing learning and completing assessments. The exploration results are as per the following: first, as far as PAI educators' getting the hang of arranging, learning apparatuses are made as per the educational program toward the start of the school year and materials are ready from important sources. Second, PAI educators should comprehend homeroom the board and utilize different learning approaches in carrying out PAI realizing with the goal that understudies are blissful and roused to learn. Third, to evaluate understudies, PAI educators should utilize mental and full of feeling appraisals. To do this evaluation they need to bring up a lattice of issues and assess the outcomes, investigate the outcomes, and give remediation to understudies who have not finished them.